Health service availability and Infection prevention status in hospitals of Nepal during transition phase of COVID-19 case surge. - Bhattarai,Suraj (2020)
SUMMARY: Background: As with other coronavirus-affected countries, Nepal's medical fraternity also expressed concerns regarding national public health strategies and hospital readiness in response to upgoing case surge. The clinicians and public health experts were particularly concerned about the government's weak preparation and unclear strategies around molecular testing, contact tracing, medical procurement, resource allocation, infection prevention measures, human resource, training, risk communication, and case management. The nation's case finding strategy-case-based approach rather than community-based, was also heavily criticized calling it 'sheer under testing' for the country of 29 million population. Methods: We assessed service availability and Infection prevention status in 110 hospitals situated across all seven provinces. A cross-sectional web-based survey was sent out to the frontline clinicians working in those hospitals between 24th March and 7th April 2020. Only one response per hospital was analyzed. Hospitals were divided into small, medium, and large based on the total number of beds (small:15; medium:16-50; large:>50), and further categorized into public, private, and mixed. Informed consent was obtained from each study participant. To maintain privacy and confidentiality, participants were asked to provide their work district name and hospital type, however, not obliged to provide hospital name and other personal information. Ethical approval was obtained from Nepal Health Research Council. Key Findings:  The survey covered 52 out of 77 districts of seven provinces.  Out of 110 hospitals under survey, 27 were small, 28 were medium, and 55 were large. These represented public (65), private (31), and public-private mixed (14) services.  Isolation beds: Out of 110 hospitals, 81% of small, 39% of medium, and one-third (33%) of large hospitals had not allocated isolation beds. Of all large hospitals, 38% had <10 beds, 18% had 10-20 beds, and 11% had >20 beds.  ICU unit: All small, majority of medium (89%), and 50% of large hospitals did not have a functional intensive care unit (ICU) at the time of study.  ICU beds: Out of 24 large hospitals that had functional ICU unit, 17 (71%) had less than 5 beds, ten had 6-15, four had 16-25, and only three had more than 25 beds that could be utilized by COVID-19 patients whenever there was a need.  Laboratory services: Majority of the small (85%) and more than half of the medium (54%) hospitals were found to have no capacity to collect patient's respiratory specimens. Among 39 (71%) large hospitals that started collecting samples, 24 had inadequate, eight had partially adequate, and only seven had adequate lab service capacity.  Test equipment: Nasopharyngeal(NP)/throat swab kits were available in one-third (35/110), whereas viral transport media (VTM), portable fridge box, and refrigerator were available in one-fifth (20%) of hospitals. Only one hospital (large/tertiary) had a functional PCR machine as of 7th April 2020.  Human resource for pandemic: A qualified General practitioner (MDGP) was providing service in more than half of medium and large hospitals. But, other health cadres crucial during pandemic response-physicians and nurses trained in Infectious disease, microbiologists, public health specialists, and clinical epidemiologists, were on board in less than 20% of hospitals. Majority of small and medium hospitals did not have a molecular biologist (laboratory technologist) for specimen collection and processing.  IPC measures for healthcare workers: Supplies of simple face mask, gloves and hand sanitizers were adequate in the majority of hospitals, however, N95-respirators, Filter masks, and PPE-suits were grossly lacking. Majority of small (24/27), medium (22/28), and large (49/55) hospitals did not have an arrangement of whole-body protective gears (PPEs) for health workers. Public facilities had a relatively better PPE availability than non-public facilities: small:12% vs. 10%; medium:26% vs. none; large:16% vs. 7%.  IPC measures in health facilities: Thermal gun temperature check service was available in half of the hospitals (54/110), and the availability was relatively better in public than in non-public sector for small (35% vs. 10%) and medium hospitals (65% vs. 60%), but better in non-public than in public sector for large hospitals (60% vs. 44%). Nearly half of the facilities had set up 'Health Information Desk', one-fourth (24%) had adopted disinfection techniques, and one-fifth (19%) had a proper waste disposal mechanism.  Government's COVID-19 support: Until mid-April, majority of hospitals had not received government's COVID-19 support (training, case referral/reporting mechanism, protective gears, laboratory equipment, funding). Public facilities were found better supported than private in terms of HEIC materials (35% vs. 26%).  Province-wise results: Bagmati had the highest number of hospitals (17/33) with ICU service, followed by Province 1 (6/19). Very few hospitals had more than 16 ICU beds: two in Province 1; three in Bagmati; two in Gandaki. Likewise, majority (75-91%) of hospitals in all provinces reported unavailability of PPE for health workers. VTM was also grossly lacking. In provinces 2 and 5, only one hospital reported VTM stock. Overall, the government's COVID-19 support was unevenly distributed across provinces; facilities in Province 2, Gandaki, and Province 5 received fewer resources than others. Conclusions and Recommendations:  The study found inadequacy in several aspects of health services and IPC measures in hospitals that define 'readiness' in the context of COVID-19 case surge.  Nepalese and other governments should, therefore, act early and proactively during health emergencies and not wait until the disease disrupts their health systems.  Other countries with similar economy levels may undertake similar surveys to measure and improve their pandemic response. Key words: Hospital readiness, infection prevention and control, health services, COVID-19, pandemic response, Nepal